2017
DOI: 10.1038/cddis.2017.547
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin promotes EGF-induced EMT in pancreatic cancer cells via Integrin/EGFR-ERK/MAPK signaling pathway

Abstract: Our previous study showed that Calreticulin (CRT) promoted the development of pancreatic cancer (PC) through ERK/MAPK pathway. We next investigate whether CRT promotes EGF-induced epithelial–mesenchymal transition (EMT) in PC via Integrin/EGFR-ERK/MAPK signaling, which has not been reported yet to our knowledge. EGF simultaneously induced EMT and activated Integrin/EGFR–ERK/MAPK signaling pathway in 3 PC cells. However, CRT silencing significantly inhibited EGF function, including inhibiting EGF-induced EMT-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 58 publications
6
113
0
Order By: Relevance
“…The MAPK signaling pathway plays a role in EMT of the various kinds of epithelial cells and includes JNK, p38 MAPK and ERK [23-25]. We observed a robust increase of the phospho-p38, and phospho-ERK in the HG-treated NRK-52E cells compared with the control group (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…The MAPK signaling pathway plays a role in EMT of the various kinds of epithelial cells and includes JNK, p38 MAPK and ERK [23-25]. We observed a robust increase of the phospho-p38, and phospho-ERK in the HG-treated NRK-52E cells compared with the control group (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Numerous studies have shown that specific molecules can affect the tumorigenesis, progression, incursion as well as migration of pancreatic cancer by participating in the regulation of JAK/STAT pathway . MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes . For the two drugs that were identified in our current study, no previous studies have identified their functions on cancer treatment.…”
Section: Discussionmentioning
confidence: 88%
“…[41][42][43][44] MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes. [45][46][47][48][49][50][51] For the two drugs that were identified in our current study, no previous studies have identified their functions on cancer treatment. These two drugs as the targeted agents for pancreatic cancer remain to be confirmed by further research as well as clinical trials.…”
Section: Discussionmentioning
confidence: 96%
“…This phenomenon for GRP78 was familiar to us 20 ; however, this was the first time that BCAP31 has been associated with the differentiation and malignancy of NSCLC, which may be due to BCAP31 exhibiting stemness functionality 21 . Survival prediction efficiency of NSCLC patients improved as more markers were included, suggesting that BCAP31 might play a similar role to the other three markers in promoting cancer metastasis 22,23 .…”
Section: Discussionmentioning
confidence: 99%